Shotgun metagenomic profiling reveals Bacillus-dominated bacterial communities in urban rooftop and surface garden soils of Bangladesh - M. Nazmul Hoque; Md. Liton Rana; Md Abu Ahsan Gilman; Pritom Kumar Pramanik; Md. Saiful Islam; Sadia Afrin Punom; Rabith Rahman; Jayedul Hassan; Tofazzal Islam; Srinivasan Ramasamy; Pepijn Schreinemachers; Ricardo Oliva; et al. (PLoS ONE, 2026)
Urban rooftop and surface garden systems play a critical role in food security in densely populated regions, yet their soil microbiomes remain understudied. To date, no baseline data exists on rooftop and surface garden soil microbiomes in Bangladesh. Understanding these communities is vital for enhancing soil health, nutrient cycling, and resilience for sustainable, climate-adapted urban agriculture. This study therefore investigated the bacterial diversity and community structure of rooftop and surface garden soils across Dhaka and Gazipur, Bangladesh. The goal was to uncover location- and garden-type-specific patterns that influence soil functionality. Using shotgun metagenomics of 27 garden soil samples (seven Dhaka rooftop [DRG], six Dhaka surface [DSG], eight Gazipur rooftop [GRG], and six Gazipur surface [GSG]), we identified 755 bacterial species dominated by Firmicutes (65–83%) and Proteobacteria (3–25%). While alpha diversity was consistent across sites (p > 0.05), beta diversity revealed distinct community structuring (p = 0.017), with surface gardens harboring greater bacterial richness (DSG:717, GSG:750 species) and elevated Bacteroidota (DSG:11.5%, GSG:2.7%) compared to rooftop soils. Strikingly, Bacillus species dominated all soils (>53% relative abundance) but exhibited location-specific distributions. DRG soils were notably enriched with B. paralicheniformis (28.3%) and B. licheniformis (25.2%). In contrast, DSG was characterized by B. cereus sensu lato (16.0%), Brevibacillus agri (12.1%), and Flavobacterium thermophilum (11.4%). GRG soils were dominated by B. cereus sensu lato (42.4%) and B. agri (11.5%). GSG soils showed diverse Bacillus species, including B. stratosphericus (14.6%), B. licheniformis (12.7%), B. safensis (9.7%), and B. altitudinis (8.8%). Of 41 detected Bacillus species, more than 58.0% were shared across gardens, yet their abundances varied with microhabitat. Moreover, KEGG profiling revealed marked functional divergence among urban garden soils. Carbohydrate metabolism dominated all sites (9.30–11.07%). DRG was uniquely enriched in photosynthesis (8.40%) and methane metabolism (8.62%), whereas DSG, GRG, and GSG showed higher oxidative phosphorylation (3.75–4.08%), two-component systems (3.24–3.73%), and biosynthetic pathways. This study unveils the ecological dominance of Bacillus species in urban agricultural soils, with location-driven compositional and functional shift. These findings are pivotal for optimizing sustainable urban agriculture in rapidly developing regions, where soil bacteriomes can be harnessed to improve crop resilience and food security.